Peringatan satu suro di kota malang: Menjaga tradisi dan budaya - Amanah, Amanda Luthfi (Maliki Interdisciplinary Journal, 2025)
The commemoration of Satu Suro in Malang City is an important tradition that illustrates the richness of local culture and community spirituality. This activity, which coincides with the Hijriah New Year, involves various events such as offering offerings on the Brantas River, Suroan cultural carnivals, group prayers, grand recitations, as well as traditional exhibitions and bazaars. The procession of offering offerings symbolizes an expression of gratitude and a request for safety, while the cultural carnival displays the beauty of traditional clothing and traditional art. Joint prayers and large recitations strengthen the faith of Muslims and strengthen ties between residents. Exhibitions and bazaars provide space for the promotion of local products and cultural education for the younger generation. Through this commemoration, the people of Malang City are trying to protect and preserve the cultural heritage inherited from their ancestors. The commemoration of Satu Suro is not just ceremonial, but also a form of appreciation for the identity and identity of the nation, as well as the hope that it will continue to be passed on to future generations.